PROFESSIONAL INTERESTS AND STRATEGIC FLEXIBILITY: A POLITICAL PERSPECTIVE ON ORGANIZATIONAL CONTRACTING - Goodstein, Jerry; Boeker, Warren; Stephan, John (Strategic Management Journal, 1996)
In this research we consider the interrelationships between professional interests and strategic flexibility. We specifically consider how the relative power of professional and managerial interests facilitate or constrain organizational contracting with external suppliers and providers. We explore these issues by focusing on hospitals competing in the health care industry during a period of heightened competitive and regulatory change. Our findings suggest that professional interests significantly influence the degree of external contracting. These findings have important implications for maintaining strategic flexibility in highly competitive environments.